H2 ROBUST FILTERING WITH OPTIMALITY GAP CERTIFICATION - Geromel, José C. (IFAC Proceedings Volumes, 2007)
In this paper H2 robust filtering is considered. Particular attention is devoted to what we call optimality gap certification of robust filters for both continuous and discrete time invariant systems subject to polytopic parameter uncertainty. After a brief discussion on some of the most expressive methods available for H2 robust filter design, a new one based on a performance certificate calculation is presented. The performance certificate is given in terms of the gap produced by the robust filter between lower and upper bounds of a minimax programming problem where the H2 norm of the estimation error is maximized with respect to the feasible uncertainties and minimized with respect to all linear, rational, stable and causal filters. The calculations are performed through convex programming methods developed to deal with linear matrix inequality (LMI). Many examples borrowed from the literature are solved and it is shown that the proposed method outperforms all other designs.